Transisi Spin dalam Spesies Turunan Tris[2-(Pirazol-3-il)piridina]besi(II) - Djulia Onggo; Kristian H. Sugiyarto (Institut Teknologi Bandung, 1999)
Complexes [Fe(3-pp)3][X]2.2H2O, where 3-pp = (2-(pyrazol-3-yl)pyridine, and X = I, Br, NO3, and CF3SO3, and X2 = [Fe(CN)5(NO)], have been isolated and characterized in terms of magnetic, Mössbauer, and electronic spectral properties. All the dihydrate salts which were isolated from aqueous solution are red brown, and heating up to 110 - 1600C results in decomposition for all salts except for the triflate which gives complete dehydration to the anhydrous yellow salt. At room temperature, the magnetic moment of the dihidrate salts are slightly higher than the purely low-spin value (2,0-2,5 BM). The magnetic moments change gradually parallel to the change in temperature within 90 - 363K, and this is associated with the continuous spin state - singlet (1A1)quintet (5T2) - transition in iron(II). For the yellow anhydrous triflate salt, the spin state transition occurs dramatically, being discontinuous and associated with hysteresis (Tc↓ = 229K, Tc↑= 241K ; âTc = 12K ). The triflate salt also shows a termochromic nature, being yellow at room temperature and dark red-brown at low temperature.